Analyzing Character Values Presented In “English For Nusantara” Textbook For Grade Viii Of Junior High School - Siti Dian Nita; Mansyur Srisudarso; Evi Karlina Ambarwati (Jurnal Ilmiah Wahana Pendidikan, 2026)
Textbooks play a vital role in the teaching and learning process, including in English language instruction. In addition to serving as informational resources, textbooks contribute to the cultivation of students’ character values. Since 2010, the Indonesian Ministry of Education and Culture has established eighteen character education values as part of the national curriculum. This study aims to analyze the character values embedded in the English for Nusantara textbook for eighth-grade junior high school students. Employing a qualitative approach, the study utilizes content analysis to examine both verbal and visual elements within the textbook. Data were collected using a checklist instrument based on the eighteen character values and analyzed to determine the presence and representation of these values in each unit of the book. The findings reveal that all character values are reflected through verbal content such as instructions, statements, and comic strips as well as visual elements, particularly picture illustrations. However, some inconsistencies and limited representations of values were identified across chapters. Overall, English for Nusantara effectively integrates character education and serves as a meaningful tool for developing students’ moral character. This study is expected to contribute to educators, researchers, and textbook writers in designing character-based instructional materials.